Towards realistic power performance and techno-economic performance of wave power farms: The impact of control strategies and wave climates. (15th March 2022) - Wang, LiGuo; Zhao, Tao; Lin, MaoFeng; Li, Hui
Abstract: This paper performs an investigation of power performance and techno-economic performance of wave power farms in realistic wave climates, where hydrodynamic interaction and influence of control strategies employed by power take-off systems are fully considered in mathematical modeling and numerical analysis. This is of great significance for a commercial wave power farm operated in a specific sea site over a long time of years, as wave energy converters will encounter a wide range of sea states, which requires that associated power take-off systems of individual units must be controlled accordingly to maximize the converted energy and to reduce the levelized cost of energy (LCOE). To that end, a fully-coupled numerical model, where the power take-off systems of wave energy converters are coordinately controlled/tuned for each sea state by employing an optimal linear passive control strategy and an optimal active control strategy, respectively. Numerical results show that power performance and LCOE of wave power farms vary over wave climates, and machinery constraints of power take-off force must be considered. Globally coordinated control of wave power farms by employing a constrained optimal linear active control strategy yields a LCOE of 0 . 17 − 0 . 54 $/kWh and increases the annual energy generation at least three times in specific wave climates of China, United States, Australia and Ireland. Highlights: Full hydrodynamic interaction of individual wave energy converters is considered. Energy generation of wave power farms in realistic wave climates is maximized. Individual wave energy converters are coordinately controlled. Machinery constraints of power take-off systems are considered.